Inovasi Aplikasi Bebaya untuk Pemulihan Perekonomian UMKM di Kota Samarinda - Gusti Naufal Rizky Perdana; Bambang Irawan; Muhammad Nizar Hidayat (Research and Development Agency Ministry of Home Affairs, 2023)
This research was conducted to maintain the existence of MSME players amid the development of digitalization and the Covid-19 pandemic by implementing public sector innovation in empowering MSMEs. The aim is to describe and analyze the innovation of implementing a practical Bebaya application by the Samarinda City Communication and Informatics Office and identify the factors that hinder this innovation. This research uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results showed that the innovation of the Bebaya application was to the characteristics of innovation. However, there were inhibiting factors such as lack of coordination and communication in innovation development, lack of knowledge and community participation, inaccurate socialization and promotion, decreased transactions due to uneven distribution of innovative products, and not covering all levels of society. This research implies the need for increased coordination and communication, increased community knowledge and participation, more appropriate socialization and promotion, and consistent distribution of innovative products to support MSME empowerment. By overcoming these inhibiting factors, the innovation of the Bebaya application can be more effective in maintaining the existence of MSME players in the era of digitalization and the Covid-19 pandemic.